Effect of Durian Rind Nanocellulose Addition on the Vickers Hardness of Self-Cure Acrylic Resin Fabricated By Spray-on Method - Dian Noviyanti Agus Imam; Ryana Budi Purnama; Rinawati Satrio; Mutia Rochmawati (Medical and Health Journal, 2026)
Self-cure acrylic resin is commonly used to fabricate orthodontic baseplates in removable appliances. However, it exhibits relatively low hardness, making it susceptible to wear and deformation under masticatory forces. The addition of reinforcing materials can enhance mechanical properties such as hardness. Nanocellulose derived from durian (Durio zibethinus Murr.) rind, an agricultural waste product, is a promising bio-based reinforcing material. This study aimed to determine the effect of durian rind nanocellulose addition on the Vickers hardness of self-cure acrylic resin fabricated using the spray-on method.This laboratory experimental study employed a posttest-only control group design. Durian rind nanocellulose was synthesized via acid hydrolysis and characterized using Transmission Electron Microscopy (TEM) and Fourier Transform Infrared Spectroscopy (FTIR) to confirm morphology and functional groups before incorporation into the acrylic resin. The nanocellulose was dispersed in monomer using ultrasonic homogenization for 5 minutes to ensure uniform distribution, then applied to polymer powder using the spray-on method. Twenty-four samples were divided into three groups (n=8): 2% nanocellulose, 3% nanocellulose, and control (0% nanocellulose). The highest mean hardness value was found in the 2% nanocellulose group (30.77 ± 1.03 VHN), while the lowest was in the control group (26.90 ± 0.79 VHN). Data were normally distributed and homogeneous (Shapiro-Wilk and Levene tests). One-way ANOVA revealed significant differences among groups (p<0.05), with post hoc LSD tests confirming significant pairwise differences. This study concludes that durian rind nanocellulose addition significantly increases the Vickers hardness of self-cure acrylic resin fabricated by the spray-on method compared to the control group